De Novo and Relapsing Glomerulonephritis following SARS-CoV-2 mRNA Vaccination in Microscopic Polyangiitis. (22nd October 2021) - Davidovic, Tamara; Schimpf, Judith; Sprenger-Mähr, Hannelore; Abbassi-Nik, Armin; Soleiman, Afschin; Zitt, Emanuel; Lhotta, Karl
Abstract : Vaccination against SARS-CoV-2 is the most important advance in the fight against the ongoing coronavirus pandemic. Recent case reports show that the SARS-CoV-2 vaccines can very rarely cause de novo or relapsing glomerular disease. Here, we report two female patients with microscopic polyangiitis, who developed severe glomerulonephritis after immunisation with the BNT162b2 mRNA vaccine. One patient with a possible ongoing but undiagnosed disease developed severe necrotising glomerulonephritis after the second vaccination. In the other patient with a long-lasting disease, rituximab maintenance therapy had been postponed because of the coronavirus pandemic. She noted macrohematuria immediately after the second vaccine dose and developed a severe renal relapse leading to end-stage kidney disease. We suggest that patients with ANCA-associated vasculitis be carefully monitored for disease activity immediately before and after receiving the SARS-CoV-2 vaccination, especially if maintenance therapy has been interrupted. Ultimately, mRNA vaccines should probably be avoided in these patients.